Effects of Pulmonary Rehabilitation on Exercise Tolerance in Patients with COPD - Ahmed, Mohammad Nesar Uddin; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2015)
Background: Pulmonary rehabilitation (PR) is known to be therapeutically useful for COPD patients. Objective: To evaluate the effects of combination of breathing exercises (pursed lip breathing and diaphragmatic breathing) and lower extremity endurance training (LEET) as part of PR program on six minute walk distance (6MWD), on oxygen saturation (SpO2%), on the level of dyspnea and fatigue in patients with moderate stable COPD. Methods: This prospective study was conducted in the Department of Physiology, BSMMU, Dhaka from July 2010 to June 2011 on 116 male stable moderate COPD patients aged 50 to 65 years. They were enrolled from the out patient department (OPD) of the Department of Medicine of BSMMU and NIDCH Dhaka. 56 patients without PR constituted control group and experimental group included 60 patients intervened with PR. The experimental patients were advised to perform the PR program for 30 minutes duration per session at home twice daily, for consecutive 60 days along with the standard drug treatment of COPD. The control patients were advised to continue their standard drug treatment alone for consecutive 60 days. For the assessment of exercise tolerance, 6MWD, SpO2%, the level of dyspnea and fatigue of all subjects were recorded on day 0 and day 60 for both the groups. SpO2% was recorded by portable Pulse Oximeter and the level of dyspnea as well as fatigue were recorded by Modified Borg Scale. Statistical analysis was done by independent sample t test and paired sample t test. Results: Significant improvement were observed in 6MWD, SpO2%, the level of dyspnea and fatigue in patients who performed PR program. In addition, significant improvement in these parameters were observed after completing PR program compared to the beginning of the intervention. Conclusion: The study concludes that regular exercise of all components of PR program significantly improve exercise tolerance in COPD patients DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22799 Bangladesh Soc Physiol. 2014, December; 9(2): 65-71